Réponses

Meilleure réponse !
2012-11-02T00:50:31+01:00

Exercice 3

 

1) (5+\sqrt{2})^{2} = 25 + 2 + 5\sqrt{2} = 27 + 5\sqrt{2}

 

2) NP^{2} = (\sqrt{10}+\sqrt{5})^{2}+12 = 10+5+2\sqrt{50}+12\\=27+5\sqrt{2} = (5+\sqrt{2})^{2}  d'apres le 1) donc NP = 5+\sqrt{2}

 

Exercice 4

 

1)\frac{3(x-3)}{2} +\frac{x}{3}=\frac{3x}{2}-\frac{9}{2}+\frac{x}{3}=\frac{11}{6}x-\frac{9}{2}

 

2) x=-6 =>  \frac{11}{6}\times(-6)-\frac{9}{2}=\frac{-31}{2}=-15.5

 

Exercice 5

 

A= \frac{6x-1}{3x-1}-\frac{2x+5}{2-6x}=\frac{-2}{-2}\times\frac{6x-1}{3x-1}-\frac{2x+5}{2-6x}\\=\frac{2-12x-2x+5}{2-6x}=\frac{7-14x}{2-6x}

 

 Pour la B, pense à l'identitée remarquablea^{2}-b^{2}=(a+b)(a-b)

 

B=\frac{3}{x+2}+\frac{1}{x^{2}-4} = \frac{3}{x+2}+\frac{1}{(x+2)(x-2)} \\=\frac{3(x-2)}{(x+2)(x-2)}+\frac{1}{(x+2)(x-2)} = \frac{3x-5}{(x+2)(x-2)} ou=\frac{3x-5}{x^{2}-4}

 

Voili voilou ... un petit merci,un petit meilleur réponse m'encouragerais ;)